A novel approach for face privacy protection based on surveillance video in complex scene - Chi ZHANG; Ye LU; Yuping LUO; Xiaokai SUN; Hanke ZHU (Dianxin kexue)
During the process of monitoring video surveillance, potential risks of leaking personal privacy information may occur due to the exposure of facial information to the surveillance video.It is necessary to mosaic the pedestrian privacy information in the real-time video stream.At present, the commonly used coding method based on face detection is heavily affected by pedestrian appearances and illumination, which often leads to weak real-time performance and undetected errors.To solve the problems above, a multi-detection model was proposed, combining face detection algorithm, target object detection algorithm and pre-frame association detection method, and compared with the traditional face detection model.Experimental results show that the recall rate of the proposed model is 532% higher than that of the traditional face detection algorithm.